1999
DOI: 10.1093/humrep/14.10.2442
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized clinical trial comparing 150 IU recombinant follicle stimulating hormone (Puregon®) and 225 IU highly purified urinary follicle stimulating hormone (Metrodin-HP®) in a fixed-dose regimen in women undergoing ovarian stimulation

Abstract: A prospective, randomized, open, multicentre (n = 3) study was conducted to compare the efficacy and efficiency of a fixed daily dose of 150 IU (3x50 IU) recombinant follicle stimulating hormone (recFSH, Puregon((R))) and 225 IU (3x75 IU) highly purified urinary FSH (uFSH-HP, Metrodin-HP((R))) in women undergoing ovarian stimulation prior to in-vitro fertilization treatment. A total of 165 women were treated with FSH, 83 subjects with recFSH and 82 subjects with uFSH-HP. In the recFSH group a mean number of 8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(15 citation statements)
references
References 13 publications
2
11
0
2
Order By: Relevance
“…Compared with the standard dosage of 225 IU of gonadotropins per day, the lower dose of 150 IU used in mild stimulation cycles demonstrates equivalent, not lesser pregnancy rates (19)(20)(21). Hohmann et al (22) demonstrated in a prospective randomized trial that although mild stimulation results in a lower number of oocytes, it is associated with a higher chance of conceiving.…”
Section: Mild Stimulationmentioning
confidence: 99%
“…Compared with the standard dosage of 225 IU of gonadotropins per day, the lower dose of 150 IU used in mild stimulation cycles demonstrates equivalent, not lesser pregnancy rates (19)(20)(21). Hohmann et al (22) demonstrated in a prospective randomized trial that although mild stimulation results in a lower number of oocytes, it is associated with a higher chance of conceiving.…”
Section: Mild Stimulationmentioning
confidence: 99%
“…, T − 1, can be up to six (6) ampoules for poor responders (Hofmann et al 1989). However, 2 and 3 ampoules are commonly adopted in clinics (Hoomans et al 1999;Wikland et al 2001). In the literature survey by Rombauts (2007), only for the poor-responsive patients does 4 ampoules initialized.…”
Section: The Decision Variablesmentioning
confidence: 99%
“…However, some factors may influence the performance of FSH on these cells, as the source of FSH, which is directly related to their degree of purification and biological activity. This hormone may be extracted from the urine of women after menopause (HOOMANS et al, 1999), the pituitary extract of domestic animals, especially porcine (pFSH) and sheep (oFSH), and by recombinant DNA technology using ovarian lineage chinese hamster cells for recombinant human FSH; rhFSH (CALDER et al, 2003). Same after purification, urinary FSH or derived from pituitary displays a low degree of purity, with varying amounts of other hormones related to fertility, primarily LH (HOOMANS et al, 1999;LISPI et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This hormone may be extracted from the urine of women after menopause (HOOMANS et al, 1999), the pituitary extract of domestic animals, especially porcine (pFSH) and sheep (oFSH), and by recombinant DNA technology using ovarian lineage chinese hamster cells for recombinant human FSH; rhFSH (CALDER et al, 2003). Same after purification, urinary FSH or derived from pituitary displays a low degree of purity, with varying amounts of other hormones related to fertility, primarily LH (HOOMANS et al, 1999;LISPI et al, 2006). When it comes to origin FSH for IVM of bovine oocytes, the most used are of porcine origin with different proportions of FSH:LH (ALVES et al, 2001;CALDER et al, 2003;KAKKASSERY et al, 2010).…”
Section: Introductionmentioning
confidence: 99%